Creating a life worth living : a practical course in career design for aspiring writers, artists, filmmakers, musicians, and others who want to make a living from their creative work /: a practical course in career design for aspiring writers, artists, filmmakers, musicians, and others who want to make a living from their creative work. (©1997) - Unknown
No abstract available